Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian Menggunakan Metode Servqual Di Puskesmas Kecamatan Gadingrejo - Yulinda, Gita; Pratiwi, Mida; Yanti, Erna; Putri, Diah Kartika (Peneliti.net, 2025)
Patient satisfaction with medical services can be raised by providing high-quality pharmaceutical services. Although Wates Public Health Center and Gadingrejo Public Health Center already have suggestion boxes to gauge patient satisfaction with services rendered, the program's implementation is lacking since patients are less likely to voice their opinions and because patient expectations and the services received by the facility frequently diverge. The research objective was to determine the level of patient satisfaction with pharmaceutical services at Gadingrejo Public Health Center and Wates Public Health Center and to find out whether there is a difference in the level of patient satisfaction with pharmaceutical services at Gadingrejo Health Center and Wates Health Center. This research type is descriptive with a cross-sectional method using 23 statement items on a Likert scale. The samples in this study were patients seeking treatment at the Gadingrejo Public Health Center and Wates Public Health Center with a total sample of 96 respondents. The research result was the level of patient satisfaction at Gadingrejo Health Center and Wates Health Center in all dimensions using the servqual method, namely reliability, responsiveness, assurance, empathy, and tangible facilities with an average value at Gadingrejo Public Health Center 87.31% and Gadingrejo Public Health Center Wates 88.27%. The difference test resulted in a significant value of P=0.776. In conclusion, the two public health centers' levels of patient satisfaction with pharmaceutical services, as determined by the Servqual method, fall into the